(untitled) (The Planet, 2023)
Introduction: PPD is a complicated combination ofphysical, mental, and behavioral changes that occur insome women after having birth. Postpartum depression isneither a shortcoming nor a weakness. Sometimes it’s justa side effect of giving birth. Aim of the study: The aim ofthe study was to observe the prevalence of postpartumdepression (PPD) as well as the possible risk factorsamong participants. Methods & Materials: This crosssectional observational study was conducted at theDepartment of Obstetrics and Gynecology, GonoshasthayaNagar Hospital, Dhanmondi, Dhaka, Bangladesh. Read full abstract in PDF.